Microbial composition of a hydropower cooling water system reveals thermophilic bacteria with a possible role in primary biofilm formation. Issue 2 (10th March 2021) - Reis, Mariana de Paula; de Paula, Rayan Silva; Reis, André Luiz Martins; Souza, Clara Carvalho e; Júnior, Renato Brito de Oliveira; Ferreira, Jacqueline Alves; Mota, Helen Regina; de Carvalho, Marcela David; Jorge, Erika Cristina; Cardoso, Antônio Valadão; Nascimento, Andréa Maria Amaral
Abstract: Microfouling, ie biofilm formation on surfaces, can have an economic impact and requires costly maintenance in water-powered energy generation systems. In this study, the microbiota of a cooling system (filter and heat exchanger) in the Irapé hydroelectric power plant in Brazil was examined. The goal was to identify bacteria that could be targeted to more efficiently reduce biofilm formation. Two sampling campaigns were made corresponding to two well-defined seasons of the Brazilian Cerrado biome: the dry (campaign 1) and the wet (campaign 2). Microfouling communities varied considerably over time in samples obtained at different times after the last clearance of the heat exchanger. The thermophilic bacteria Meiothermus, Thermomonas and Symbiobacterium were exclusive and abundant in the microfouling of the heat exchanger in campaign 2, while methanotrophs and iron-reducing bacteria were abundant only in filter sediments. These findings could help to guide strategies for ecofriendly measures to reduce biofilm fouling in hydroelectric power plants, minimizing environmental and economic losses.